2008
DOI: 10.1111/j.1600-065x.2008.00592.x
|View full text |Cite
|
Sign up to set email alerts
|

The microanatomy of T‐cell responses

Abstract: The priming of a T cell results from its physical interaction with a dendritic cell (DC) that presents the cognate antigenic peptide. The success rate of such interactions is extremely low, because the precursor frequency of a naive T cell recognizing a specific antigen is in the range of 1:10(5)-10(6). To make this principle practicable, encounter frequencies between DCs and T cells are maximized within lymph nodes (LNs) that are compact immunological projections of the peripheral tissue they drain. But LNs a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
128
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(134 citation statements)
references
References 117 publications
(157 reference statements)
4
128
2
Order By: Relevance
“…Dendritic cells and B cells reside in the lymph nodes, and T cells traffic through the paracortical region, the architecture of which is optimized for rapid cell trafficking to help naive T cells to make contact with thousands of dendritic cells to find their APC partners 9 . Immature dendritic cells patrol peripheral tissues and then migrate to the lymph nodes after they take up antigen, but the lymph nodes also contain many immature dendritic cells that constantly sample antigens carried through the lymph nodes by lymph drained from the peripheral tissues; the latter population of dendritic cells may function mainly for the purpose of maintaining tolerance 4 .…”
Section: Tissue and Cellular Targetsmentioning
confidence: 99%
“…Dendritic cells and B cells reside in the lymph nodes, and T cells traffic through the paracortical region, the architecture of which is optimized for rapid cell trafficking to help naive T cells to make contact with thousands of dendritic cells to find their APC partners 9 . Immature dendritic cells patrol peripheral tissues and then migrate to the lymph nodes after they take up antigen, but the lymph nodes also contain many immature dendritic cells that constantly sample antigens carried through the lymph nodes by lymph drained from the peripheral tissues; the latter population of dendritic cells may function mainly for the purpose of maintaining tolerance 4 .…”
Section: Tissue and Cellular Targetsmentioning
confidence: 99%
“…Studies with LN transplantation alone and in combination with growth factor therapy showed an improvement of lymphedema after lymphadenectomy in mice [18]. These results are not unexpected, since a role of LN in the regulation of peripheral fluid homeostasis is obvious [19]. The preventive effects of residual LN was shown recently and was obvious since the biopsy of the sentinel lymph node only reduced the occurrence of lymphedema [20].…”
Section: Introductionmentioning
confidence: 86%
“…However, the secondary lymphoid organs have an elaborated architecture. The details of their structural organization allow to suggest that an intensity of the transport processes, in particular, the diffusion, mediating the spread of soluble factors, in particular, IFNα, differs essentially depending on the location in the specific anatomical SLO compartments [16]. To examine the diffusion effect on the spatial distribution of IFNα we consider the concentration of the interferon I at time t to be also dependent on position x ∈ Ω ⊂ R 3 , where Ω represents the spatial region occupied by the lymphoid organ.…”
Section: Reaction-diffusion Model Of Ifn Dynamicsmentioning
confidence: 99%
“…The microanatomy of a paradigmatic SLO can be essentially reduced to three zones: the subcapsular zone, which is an APC-rich area, the B-cell activation zone (B-cell follicle) and T-cell activation zone [12]. Although direct measurements of the hydraulic conductivity within the T-cell zone are missing, it is considered that both diffusion and convection are extremely low [16]. Therefore, the spatial distribution of IFN in SLO deserves further investigation.…”
Section: Introductionmentioning
confidence: 99%